Novel Protein Glycan Side-Chain Biomarker and Risk of Incident Type 2 Diabetes Mellitus. Issue 6 (June 2015) - Akinkuolie, Akintunde O.; Pradhan, Aruna D.; Buring, Julie E.; Ridker, Paul M; Mora, Samia
Abstract : Objectives—: Enzymatically glycosylated proteins partake in multiple biological processes, including glucose transport and inflammation. We hypothesized that a novel biomarker (GlycA) of N -acetyl methyl groups originating mainly from N -acetylglucosamine moieties of acute-phase glycoproteins is related to incident type 2 diabetes mellitus and compared it with high-sensitivity C-reactive protein. Approach and Results—: In 26 508 initially healthy women free of diabetes mellitus, baseline GlycA and high-sensitivity C-reactive protein were quantified by nuclear magnetic resonance spectroscopy and immunoturbidimetry, respectively. During median follow-up of 17.2 years, 2087 type 2 diabetes mellitus cases occurred. In Cox models with adjustment for age, race, smoking, alcohol, activity, menopausal status, hormone use, family history, and body mass index, quartile 4 versus 1 hazard ratios and 95% confidence intervals were 2.67 (2.26–3.14) for GlycA and 3.93 (3.24–4.77) for high-sensitivity C-reactive protein; both P trend <0.0001. Associations for GlycA and high-sensitivity C-reactive protein were attenuated after additionally adjusting for lipids: 1.65 (1.39–1.95) and 2.83 (2.32–3.44), respectively, both P trend <0.0001, and after mutual adjustment: 1.11 (0.93–1.33; P trend=0.10) and 2.57 (2.09–3.16; P trend<0.0001), respectively. Conclusions—: Our finding of an association between a consensus glycan sequence common to a host of acute-phase reactants and incident type 2 diabetes mellitus provides further support for inflammation in the development of type 2 diabetes mellitus. Additional studies exploring the role of enzymatic glycosylation in the prevention of type 2 diabetes mellitus are warranted. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00000479. Abstract : Supplemental Digital Content is available in the text.